Research Tactics for Constructing Perceptions of Subject Matter in Organizational Contexts: An Ethnographic Study of Technical Communicators - Hovde, Marjorie Rush (Technical communication quarterly, 2001)
Theories of invention often overlook the role of learning subject matter in order to write, especially in workplaces. This ethnographic study describes technical communicators' abilities to learn about software within organizational constraints and resources. These writers' tactics for learning software included using it themselves, talking to co-workers, studying program specifications, learning from comments on internal reviews, and studying old manuals. I evaluate each tactic for its usefulness in creating rich knowledge. Knowing how to adapt subject matter research to one's organizational context should prove useful to novice technical communicators. This research can also help explain processes of creating knowledge in discourse.